Impedance Analyses of Alumina-Molybdenum (Al2O3-Mo) Composites - Hussain, S.; Sbaizero, O. (Dhaka University Journal of Science, 2012)
The microstructure and electrical properties of Al2O3-Mo composites were investigated. Different amounts of molybdenum (5, 10, 20, 25 vol%) were added to alumina matrix and the resulting mixture was hot pressed to produce dense metal toughened-ceramic composites. The electrical properties of the composites were examined using impedance spectroscopy in the temperature range 250° C - 1000° C at 50° C temperature intervals. From the analysis, two readily resolvable arcs were found to be present: the one at higher frequencies is the intragranular (grain) response of the bulk; the other is the intergranular (grain boundary) response caused in the internal surfaces of polycrystalline specimens at low frequencies. The effects of grains and grain boundaries on the electrical properties of the composites vary with the composition and temperature. The temperature and composition dependence of grain and grain boundary conductivities are explained by the microstructure. DOI: http://dx.doi.org/10.3329/dujs.v60i2.11533 Dhaka Univ. J. Sci. 60(2): 277-281, 2012 (July)